Logan Causey: capstone - Causey, Logan, artist (Colorado State University. Libraries, 2023)
The artist's statement: Carl Jung is a psychoanalyst whose ideas and writings primarily deal with the symbology of dreams, the unconscious, and using both to learn more about oneself; Jung's notions have strongly impacted my approach to image-making. Similar to psychoanalysis, my work centers around the theme of exploration and uncovering the hidden, which is typically dismissed or forgotten about. My images are strongly connected to domestic spaces that are not seen as having conventional appeal or beauty, they are off the beaten path and must be deliberately pursued to be found. Analog image-capture is an extremely significant aspect of my work as it emphasizes process and encourages a multi-layered methodology when making photographs, this extra focus on process is significant to my work as it is linked to Carl Jung's process of individuation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making